Spirit : stallion of the Cimarron [videorecording (DVD)] - Asbury, Kelly; Cook, Lorna; Damon, Matt; Cromwell, James; Studi, Daniel (DreamWorks Home Entertainment, 2002)
Join Spirit, a young wild mustang, as he sets out against impossible odds to regain his freedom and save his homeland. On his courageous journey across the American frontier, Spirit forms a remarkable friendship with a Lakota brave, outwits a squadron of soldiers, and falls for a paint mare named Rain.